Комплексообразование Cu (II) с 4-(2-пиридилазо)-резорцином - Калиниченко, И.Е.; Выщеревич, И.В. (Украинский химический журнал, 2006)
Методами спектрофотометрии и растворимости изучено комплексообразование Cu (II) с 4-(2-пиридилазо)-резорцином в водных растворах при 20 °С и ионной силе 0.1. Определены константы ионизации лиганда, устойчивости комплексов состава CuHR⁺, CuR, Cu(HR)₂, CuRHR⁻, CuR₂²⁻ и образования осадка Cu(HR)₂. Методами спектрофотометрії та розчинності вивчено комплексоутворення Cu (II) з 4-(2-піридилазо)-резорцином в водних розчинах при 20 °С і йонній силі 0.1. Визначено константи йонізації ліганду, константи стійкості комплексів складу CuHR⁺, CuR, Cu(HR)₂, CuRHR⁻, CuR₂²⁻ та утворення осаду Cu(HR)₂. The spectrophotometric and solubility methods are used to study the complex formation of Cu (II) with 4-(2-pyridylazo)resorcinol in aqueous solutions at 20 °C and ionic strength 0.1. The ligand ionisation constants, the stability constants for the CuHR⁺, CuR, Cu(HR)₂, CuRHR⁻, CuR₂²⁻ complexes and for the Cu(HR)₂ precipitation are determined.